Implementasi Undang-Undang Tindak Pidana Pencucian Uang dalam Kasus Investasi Di Plaftorm Binomo untuk Mewujudkan Keadilan Bagi Korban - Nugroho, Dryan; Firmansyah, Hery (UNES Law Review, 2023)
This research analyzes the implementation of the Anti-Money Laundering Law in the case of illegal investment on the Binomo platform. The investigation involves alleged violations of the ITE Law, the Money Laundering Law, the Indonesian Criminal Code, and futures trading regulations related to illegal investments causing financial losses to victims. Reports from the public have led to legal actions involving the Indonesian National Police's Criminal Investigation Department (Bareskrim Polri) concerning these investment-related legal violations. Following their identification as suspects, victims of illegal investment have filed claims for compensation, while institutions such as the Witness and Victim Protection Agency (LPSK) have provided information on restitution or compensation available under Law No. 31 of 2014. This case also highlights the role of applications like Binomo in money laundering, resulting in significant losses for the victims. Discussions encompass the modus operandi of perpetrators, government efforts in blocking related websites, and the crucial conclusion regarding the importance of robust law implementation to safeguard the public and prevent detrimental illegal practices.